Kriminalisasi Deepfake Pornography Berbasis AI dalam Perspektif Perlindungan HAM Di Era Digital - Yurike Inna Rohmawati Ciptaningrum; Moh. Muhlisin; I Gede Widhiana Suarda; Triana Ohoiwutun (PT. Hasba Edukasi Mandiri, 2025)
The advancement of artificial intelligence technology in the digital era had a significant impact on human life, including emergence of abuse in the form of deepfake pornography. Phenomenon involves the manipulation of a person's face or voice into pornographic content without consent, which clearly violates the rights to privacy, honor, and human dignity. In Indonesia, although there are regulations such as the ITE Law, the TPKS Law, the PDP Law, and the national Criminal Code, there is no regulation that explicitly ensnares the crime of deepfake pornography. This creates a legal vacuum and serious challenges in human rights protection. This study uses a normative juridical method with legislative and conceptual approach to analyze the urgency of criminalizing AI-based deepfake pornography and formulate an ideal policy model within the Indonesian criminal law system. The results of the study suggest that criminalization is a necessary form of human rights protection that can adapt to technological developments. The ideal criminalization policy model must be comprehensive and integrative, encompassing specific criminal regulations, strengthening digital forensics, victim protection and recovery, international cooperation, and a cultural approach. Criminal law can function effectively as an instrument for protecting human rights and promoting social justice in digital era.